2017
DOI: 10.1051/0004-6361/201731483
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum radial velocity analyser (SERVAL)

Abstract: Context. The CARMENES survey is a high-precision radial velocity (RV) programme that aims to detect Earth-like planets orbiting low-mass stars. Aims. We develop least-squares fitting algorithms to derive the RVs and additional spectral diagnostics implemented in the SpEctrum Radial Velocity Analyser (SERVAL), a publicly available python code. Methods. We measured the RVs using high signal-to-noise templates created by coadding all available spectra of each star. We define the chromatic index as the RV gradient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
418
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 389 publications
(447 citation statements)
references
References 31 publications
6
418
0
3
Order By: Relevance
“…For the empirical case, we use the actual uncertainties derived from the determination of RVs. We refer to Zechmeister et al (2018) and Reiners et al (2018) for a detailed discussion. Because of major uncertainties, e.g., in the scaling of SNR (or the brightness of stars as a function of wavelength), the treatment of telluric lines, in metallicities, and in the synthetic models, we expect some disagreement between the RV photon noise limits from different sources.…”
Section: Determining Radial Velocity Photon Noisementioning
confidence: 99%
“…For the empirical case, we use the actual uncertainties derived from the determination of RVs. We refer to Zechmeister et al (2018) and Reiners et al (2018) for a detailed discussion. Because of major uncertainties, e.g., in the scaling of SNR (or the brightness of stars as a function of wavelength), the treatment of telluric lines, in metallicities, and in the synthetic models, we expect some disagreement between the RV photon noise limits from different sources.…”
Section: Determining Radial Velocity Photon Noisementioning
confidence: 99%
“…This approach is limited by the accuracy of the mask, and since most masks are built for a broad category of spectral type rather than customized for the individual star in question, it is unlikely that this technique retrieves maximally precise RVs. Deriving a custom spectral template by stacking all spectra iteratively as the RVs are determined has been shown to be a superior approach for stars with complex spectra (Anglada-Escudé & Butler 2012;Zechmeister et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Allende Prieto (2007) similarly foreshadowed aspects of our technique in terms of performing multiple pairwise comparisons, but their technique seeks only to improve RVs that have already been measured by some other technique. Our technique is also hardly the first to deliberately avoid using a synthetic template or template from a different star, and to favour instead using only the science observations themselves to construct a template; this approach has been taken elsewhere for both absorption cell spectrographs (Sato et al 2002;Johnson et al 2006;Gao et al 2016) and stabilized spectrographs (Anglada-Escudé & Butler 2012;Astudillo-Defru et al 2015;Zechmeister et al 2018), and has been demonstrated using both CCFs and ML (or least squares) approaches. HARPS-TERRA and SERVAL, which we used for RV extraction in Section 6.3, both adopt such a least-squares template matching approach.…”
Section: Conceptual Comparison With Existing Techniquesmentioning
confidence: 99%
“…While increasing attention has been paid in recent years to developing better approaches to RV extraction (e.g. Anglada-Escudé & Butler 2012;Zechmeister et al 2018;Dumusque 2018;Bedell et al 2019), the approach of cross-correlating observed spectra with a masked, weighted template (often called a delta function template when a binary mask is used) retains wide currency. For example, this approach is employed in the primary data reduction pipelines of HARPS (Rupprecht et al 2004) and HARPS-N (Cosentino et al 2012), as well as in the pipelines of newer instruments such as ESPRESSO (Di Marcantonio et al 2018) and EXPRESS (e.g.…”
Section: Introductionmentioning
confidence: 99%